PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Yogi Agustio Sayogo, 10.05.52.0051; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This study aims to provide empirical evidence about the effect of the Local Own Revenue (PAD), the General Allocation Fund (DAU) and Specific Allocation Fund (DAK) on the Capital Expenditure districts / cities in Central Java.Â The sample used in this study were 35 districts / cities in Central Java taken from the Report of Actual Income and Expenditure Budget (budget) from the years 2011-2013. Methods of data collection used in this study is whole population census methods. Analysis tool used in this study is multiple linier regression with a t test, f test, and test the coefficient of determination.Â The result of this research shows that Local Own Revenue, and General Allocation Fund has positive influence toward the Allocation Of Capital Expenditure. Besides Specifiic Allocation Fund has negative influence toward the Allocation Of Capital Expenditure.Keywords: Local Own Revenue, General Allocation Fund, Specific Allocation Fund, Capital Expenditure